Addressing climate inaction as our greatest threat to sustainable development - Mackay, S.; Hales, R.; Hewson, J.; Addis, R.; Mackey, B. (Elsevier, 2025)
More than 1 degree of global warming has been reached and once projected impacts are now being realized. Despite these impacts and the short timeframe available to avoid further warming, climate inaction remains a major threat to sustainable development. In this article, we bring a renewed focus to the issue of climate inaction. We unpack the systemic market failure that underpins current climate action efforts globally and how by shifting focus to address inaction this could be overcome. We explore how climate policies are inadvertently allowing climate inaction to persist, why this is happening and how to address it. Central to our argument is that climate policies still draw too heavily on a neoclassical development paradigm, rather than reinvigorated industrial policy, resulting in market interventions that fail to address the scale and systemic nature of the climate action challenge. We therefore reorient climate policies towards addressing inaction as a systemic development challenge that demands a stronger role from the government. We conclude by proposing a market systems framework for guiding policymakers to better target the systemic nature of climate inaction and the threat it poses to sustainable development.